THERAPEUTIC INDICES OF SOME ANTIFUNGAL ORGANIC COMPOUNDS - J. NIDIRY, EUGENE SEBASTIAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to evaluate the therapeutic indices (TIs) some antifungal organic compounds and to compare their safety. Methods: TIs of 55 organic compounds were evaluated by dividing their mammalian toxicity values given as median lethal doses ([mg/kg] rat, oral) collected from literature by experimentally determined fungitoxicity values evaluated as median effective concentration (EC50 [mg/L]) for the mycelial growth inhibition of Colletotrichum gloeosporioides on potato dextrose agar medium. Results: Large variations in TIs are observed in different classes of compounds, namely, alcohols, carboxylic acids, phenols, esters, and aldehydes. The relationship between carbon chain length of saturated monohydric alcohols and mammalian toxicity shows that toxicity increases from chain length 1 to 5, declines from 5 to 6, increases from 6 to 7, and steadily declines from 7 to 10. Thus, the relationship is by and large parabolic. The relationship between carbon chain length and molar antifungal activity is also parabolic. In spite of this, large differences are found in TIs making 1-decanol (TI=42.1) a very safe antifungal compound and 1-pentanol (TI=0.17) a hazardous antifungal compound. This is because mammalian toxicity reaches a maximum around carbon chain length of 5, while in the case of antifungal activity, it reaches a maximum around carbon chain length of 10. Conclusions: Among the 55 compounds, whose TIs were evaluated, some compounds with high TIs (>10) which can be considered safe as antifungal compounds are citronellol, geraniol, 1-decanol, 1-octanol, phenyl acetaldehyde, methyl anthranilate, 1-naphthol, 2-naphthol, and propionic acid. Some compounds with low TIs (<0.50) which can be considered hazardous as antifungal compounds are resorcinol, hydroquinone, oxalic acid, and acetyl acetone.